Towards Incorporation of Software Security Testing Framework in Software Development - Hassan, N. H.; Selamat, S. R.; Sahib, S.; Hussin, B. (Springer-Verlag Berlin Heidelberg 2011, 2011)
The aim of this paper is to provide secure software using security testing approach. The researchers have reviewed and analyzed the software testing frameworks and software security testing frameworks to efficiently incorporate both of them. Later, the researchers proposed to fully utilize the acceptance testing in software testing framework to achieve by incorporating it in software security testing framework. This incorporation is able to improve the security attribute needed during requirement stage of software development process. The advantage of acceptance test is to expose the system of the real situation, including vulnerability, risk, impacts and the intruders which provide a various set of security attribute to the requirement stage. This finding is recommended to establish a baseline in formulating the test pattern to achieve effective test priority.